Rapid Response Subunit Vaccine Design in the Absence of Structural Information - Wijesundara, Danushka K.; Avumegah, Michael S.; Lackenby, Julia; Modhiran, Naphak; Isaacs, Ariel; Young, Paul R.; Watterson, Daniel; Chappell, Keith J. (Frontiers in Immunology, 2020)
Prior to 2020, the threat of a novel viral pandemic was omnipresent but largely ignored. Just 12 months prior to the Coronavirus disease 2019 (COVID-19) pandemic our team received funding from the Coalition for Epidemic Preparedness Innovations (CEPI) to establish and validate a rapid response pipeline for subunit vaccine development based on our proprietary Molecular Clamp platform. Throughout the course of 2019 we conducted two mock tests of our system for rapid antigen production against two potential, emerging viral pathogens, Achimota paramyxovirus and Wenzhou mammarenavirus. For each virus we expressed a small panel of recombinant variants of the membrane fusion protein and screened for expression level, product homogeneity, and the presence of the expected trimeric pre-fusion conformation. Lessons learned from this exercise paved the way for our response to COVID-19, for which our candidate antigen is currently in phase I clinical trial.